Transactional Leadership Relationship, Extrinsic Motivation and Administrative Performance Staff - Azmi, Ahmad Ulul; Muhammad, Muhammad; Agus, Agus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to explain the relationship between transactional leadership, extrinsic motivation, and administrative performance of educational staff (tendik) using a literature review method. The results of the study indicate that transactional leadership has a positive effect on performance if the leader consistently implements agreements, while extrinsic motivation in the form of salary, benefits, and rewards also encourages performance improvement. Simultaneously, the two complement each other and contribute to optimizing administrative performance of educational staff.